The comparison of Monte Carlo simulations with GEANT4 for polyethylene absorber within the pCT development - Yevseyeva, Olga (2011)
Proton beams in medical applications deal with relatively thick targets like the human head or trunk. Thus, the fidelity of proton computed tomography (pCT) simulations as a tool for proton therapy planning depends in general case on the accuracy of results obtained for the proton interaction with thick absorbers. As we previously showed it, the GEANT4 simulations of proton energy spectra after thick absorbers do not agree well with existing experimental data. Moreover, the spectra simulated for the Bethe-Bloch domain showed an unexpected sensitivity to the choice of low-energy electromagnetic models during the code execution. These observations were done with the GEANT4 version 8.2 during our previous simulations for pCT. As the most probable reasons for these effects is some specific feature in the code, or some specific implicit parameters in the GEANT4 manual, we continued our study with versions 9.2 and 9.4 of the code. This work describes in more details the simulations of the 25 MeV protons passing through 6mm polyethylene absorber. The simulations were done by modifying only the geometry in the Hadrontherapy Example, and for all available choices of the Electromagnetic Physics Models. The results were compared with our previous simulation, with theoretical predictions and with experimental data. Some variations in comparison with our previous results were obtained. The simulations were performed considering further applications for pCT development.